An assessment of Ryukyu Archipelago's coral communities over a wide latitudinal range. (April 2023) - Afzal, Mariyam Shidha; Takeuchi, Konomi; Iguchi, Akira; Sakai, Kazuhiko; Dirgantara, Dio; Nakamura, Takashi
Abstract: Japan's coral reefs have changed dramatically over the last several decades due to climate change and anthropogenic impacts. Due to its dynamic location, the islands of Ryukyu Archipelago offer a unique environmental gradient to study the interactions between environmental variations, connectivity, resilience, climate change and adaptation of marine biodiversity along a wide latitudinal gradient. To obtain detailed baseline assessments of the reefs of Ryukyu Islands, we carried out Point Intercept Transect surveys to compare the assemblages of benthic communities in six regions of Ryukyu Archipelago, examining the influence of latitude gradient and emphasising on regional features. A total of 69 individual reef sites were surveyed for this study. The overall hard coral cover for Ryukyu archipelago was 22.41% ± 7.98 (Mean ± SD) from pooled dataset. The most abundant benthic assemblage for Ryukyu Archipelago was turf algae (39.72% ± 7.21) with all regions except Amami Oshima Island having overall cover above 40%. A total of 2607 individual colonies of hermatypic corals were recorded and identified up to genus level for this study where 55 genera of corals belonging to 17 families were recorded for Ryukyu Archipelago. The overall relative abundance was highest for Acroporidae family (32.22%), followed by Merulinidae family (27.69%) and Poritidae family (14.38%). Our results highlight the current condition of the reefs of Ryukyu archipelago and offers baseline data on broad scale ecosystem where future ecological change could be compared.